Antibacterial Effect of Ozonated Water on Adherent Mutans Streptococci (In Vitro) (Mustansiria Dental Journal, 2018)
To evaluate the antibacterial efficiency of ozonated water against adherent bacteria (in vitro). Ten dentin samples per group were inoculated with bacterial suspension and treated as follows: (I) untreated served as –ve control, (II) sterile distilled water for 10 seconds served as +ve control, (III) 5.25% sodium hypochlorite (Sultan-USA) for 10 seconds, (IV) 0.2% chlorhexidine (Corsodyle®, England) for 10 seconds, and (V) 4mg/L ozonated water (Ozonesolution-Enaly, USA) for 10 seconds. Swab taken from all samples and an inoculum was spread on the selective medium MSB (HiMedia, India). Count of bacteria was recorded expressed in colony forming unit (CFU) taking in consideration the dilution factor.There was high significant reduction in viable count of adherent M.S treated with ozonatd water 4mg/L compared with the other groups at P